Luminosity on development and flowering of Dendrobium nobile Lindl. - Rosa, Yara Brito Chaim Jardim; Ramos, Fernanda Zandonadi; Souza, Rosangela Guarisso de; Soares, Jackeline Schultz; Rosa Junior, Edgard Jardim; Hoffmann, Nilda Tiyoko Kobayashi; Rosa, Derek Brito Chaim Jardim; Sorgato, José Carlos (Ornamental Horticulture, 2014)
This study, conducted at Jardinocultura area of Faculdade de Ciências Agrárias of UFGD during the period from September of 2010 to August of 2011, had as aim evaluate the cultivation and flowering of Dendrobium nobile Lindl., under five levels of luminosity (83, 104, 115, 154 e 237 μmol m-2 s-1) . During 12 months the plants were irrigated and fertilized with NPK 10-10-10 and after this period they were evaluated for the number, length and diameter of pseudobulbs, being calculated the increments in relation to initial data. At flowering time it was counted the total buds, reproductive buds, vegetative buds and undifferentiated buds and registered the anthesis at each light intensity. The experimental was arranged at completely randomized design with five treatments and seven replicates with two plants and the averages were compared by Tukey test at 5% probability. All the lighting conditions were favorable to the D. nobile cultivation, being registered increases of 36,7%, 16,0% e 16,2% in the number, diameter and length of pseudobulbs, respectively. The largest number of reproductive buds was observed at 104 μmol m-2 s-1. D. nobile can be cultivated in the light conditions varying between 83 and 237 μmol m-2 s-1, recommending the luminosity of 104 μmol m-2 s-1 to promote their flowering.